Peran Resonansi Nilai dan Implikasinya Terhadap Keunggulan Inovasi Layanan: Studi Literatur - Friska Mastarida (Forum Kerjasama Pendidikan Tinggi, 2022)
This study contributes to broadening the understanding of innovation in a comprehensive service ecosystem by focusing on the role of value resonance. This study uses a qualitative research design through library research techniques. The author presents various journal publications in the field of marketing from 2010 to 2021 using a systematic literature review approach. The research findings highlight the role of value resonance and its implications in guiding efforts to integrate organizational resources in realizing service innovation excellence. This research area focuses on value resonance in relation to the integration of brands, service systems, and experience spaces. This paper provides a comprehensive understanding of the literature on the advantages of innovation in service ecosystems.